Pyrolysis characteristics and product distribution of low-rank coal with heat-carrying particles adopting TG-FTIR and a novel self-mixing down tube reactor - Yue Gao; Lanyi Sun; Yuanyu Tian (Case Studies in Thermal Engineering, 2024)
A novel self-mixing down tube (SDT) pyrolyzer has been developed, which can separate the heat carrying particles preheated in the fluidized bed from the coal, and the two can be mixed through a specific structure to instantly heat the coal particles to a predetermined temperature. The present study investigated the pyrolysis behavior of low-rank coal with hot silica sand heat-carrying particles adopting TG-FTIR. Identifies optimal conditions for maximum tar production in a laboratory-scale SDT using a significantly larger range of coal feed rates (4 kg/h). An increase in the degree of coal metamorphism increased the initial temperature and the yield of char. The tar yield from Huolinhe lignite coal (6.56 %) and Daliuta bituminous coal (7.48 %) showing a trend of first increased and then decreased with elevating the operating temperature and optimal temperature at 520 °C, respectively. The effect of coal particle size on tar yield mainly comes from the different degrees of secondary cracking caused by contact with solid heat-carrying particles as well as the differences in the content of macerals. GC‒MS spectra of tar and deposited carbon on silica sand indicated that heavy tar can easily deposit on the surface of sand and form char through polymerization reactions.